Towards an inclusive teaching and learning experiences: A case study on virtual engagement between students of world religions 1 class and selected religious leaders and scholars SCHOLARS - Abdul Jalil, Mohd. Noh; Azis, Raba'ah Syahidah (2021)
COVID19 pandemic has altered mode of teaching and learning in Malaysia and all over the world for the past two years. All physical class activities have shifted to virtual mode. Prior to the pandemic, students who are attending World Religions 1 class at the International Islamic University Malaysia (IIUM) are experiencing teaching and learning session in class as well as at a selected house of worship. With movement restriction imposed in Malaysia during this period such opportunity is no longer available. Everything is now shifted virtually. Interestingly, the advancement of technology has open with vast opportunity for the students to gain more exposure to experts outside their classrooms. Engagements with religious leaders and scholars from all over the world are made possible. Indeed, the changing of mode has contributed positively to the students’ learning experiences. They are now able to interact virtually with the experts of the religions they studied in this course. Such experiences with add value to their existing knowledge on those religions they learned in classes.